Keratinocyte autophagy enables the activation of keratinocytes and fibroblastsand facilitates wound healing. Issue 9 (2nd September 2021) - Qiang, Lei; Yang, Seungwon; Cui, Yan-Hong; He, Yu-Ying
ABSTRACT: Macroautophagy/autophagy is a cellular catabolic process that is implicated in several physiological and pathological processes. However, the role of epidermal autophagy in wound healing remains unknown. Here, using mice with genetic ablation of the essential Atg5 (autophagy related 5) or Atg7 (autophagy related 7) in their epidermis to inhibit autophagy, we show that keratinocyte autophagy regulates wound healing in mice. Wounding induces the expression of autophagy genes in mouse skin. Epidermis-specific autophagy deficiency inhibits wound closure, re-epithelialization, keratinocyte proliferation and differentiation, dermal granulation tissue formation, and infiltration of immune cells including macrophages, neutrophils, and mast cells, while it does not affect angiogenesis. Using cytokine array screening, we found that autophagy deficiency inhibits the transcription and production of the cytokine CCL2/MCP-1 by TNF. At the molecular level, TNF induces autophagic flux and the expression of autophagy genes through NFKB in epidermal keratinocytes. TNF promotes CCL2 transcription through the autophagy-AMPK-BRAF-MAPK1/3/ERK-activator protein 1 (AP1) pathway. Indeed, treating mice with recombinant CCL2 can reverse the effect of autophagy deficiency in keratinocytes. At the cellular level, we found that CCL2 induction via autophagy in keratinocytes is required not only for keratinocyte migration and proliferation but also for dermal fibroblast activation. Our findings demonstrate a critical role of epidermal autophagy in wound healing in vivo and elucidate a critical molecular machinery coordinating keratinocyte-fibroblast interaction in skin repair. Abbreviations : ACTA2/α-SMA: actin alpha 2, smooth muscle; ACTB: β-actin; ADGRE1: adhesion G protein-coupled receptor E1; AMPK: AMP-activated protein kinase; AP1: activator protein 1; AP1-RE: AP1 response element; ATG: autophagy-related; ATG16L1: autophagy related 16 like 1; BECN1: beclin 1; BRAF: B-Raf proto-oncogene, serine/threonine kinase; C5: complement C5; CCL2/MCP-1: C-C motif chemokine ligand 2; CCL3: C-C motif chemokine ligand 3; CK: cytokeratin; cKO: conditional knockout; CRTC1: CREB-regulated transcription coactivator 1; CXCL1: C-X-C motif chemokine ligand 1; CXCL2: C-X-C motif chemokine ligand 2; ECM: extracellular matrix; EGF: epidermal growth factor; FGF7: fibroblast growth factor 7; GABARAPL2: GABA type A receptor associated protein like 2; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; HBEGF: heparin binding EGF like growth factor; HPRT1: hypoxanthine phosphoribosyltransferase 1; IHC: immunohistochemical; IL1B: interleukin 1 beta; KRT10: keratin 10; KRT14: keratin 14; MAP1LC3B/LC3B-I/II: microtubule-associated protein 1 light chain 3 beta; MAPK1/3/ERK: mitogen-activated protein kinase 1/3; MKI67/Ki-67: marker of proliferation; MPO: myeloperoxidase; NFKB: NF-kappa B, nuclear factor kappa-light-chain-enhancer of activated B cells; NFKB-RE: NFKB response element; PDGF: platelet-derived growth factor; PECAM1: platelet and endothelial cell adhesion molecule 1; PRKAA1: protein kinase AMP-activated catalytic subunit alpha 1; RELA/p65: RELA proto-oncogene, NFKB subunit; shCON: small hairpin negative control ; siNC: negative control; siRNA: small interfering RNA; SP1: sp1 transcription factor; SQSTM1/p62: sequestosome 1; TGFA: transforming growth factor alpha; TGFB1: transforming growth factor beta 1; TIMP1: TIMP metallopeptidase inhibitor 1; TNF/TNF-alpha: tumor necrosis factor; TREM1: triggering receptor expressed on myeloid cells 1; WT: wild-type